Impacts of Increasing Private Charging Piles on Electric Vehicles’ Charging Profiles: A Case Study in Hefei City, China - Jian Chen; Fangyi Li; Ranran Yang; Dawei Ma (Energies, 2020)
Electric vehicles (EVs) and charging piles have been growing rapidly in China in the last five years. Private charging piles are widely adopted in major cities and have partly changed the charging behaviors of EV users. Based on the charging data of EVs in Hefei, China, this study aims to assess the impacts of increasing private charging piles and smart charging application on EVs’ charging load profiles. The charging load profiles of three types of charging piles which are public, employee-shared, and private ones, are simulated in three different scenarios. The results of scenario simulation indicate that the increase in EVs will reinforce the peak value of the total power load, while increasing private charging piles and the participation rate of smart charging piles will have peak-load shifting effects on the power load on weekdays. Specifically, 12% of the charging load will be shifted from public piles to private ones if the ratio of EVs and private piles increases from 5:3 to 5:4. The adoption of smart charging in private piles will transfer 18% of the charging load from the daytime to the night to achieve peak-load shifting. In summary, promoting the adoption of private piles and smart charging technology will reshape the charging load profile of the city, but the change will possibly reduce the utilization rate of public charging piles. The results suggest that urban governments should consider the growth potential of private piles and promote smart charging in charging infrastructure planning.